A concise and efficient synthesis of benzimidazo[1,2-c]quinazolines through CuI-catalyzed intramolecular N-arylations - Pang, Xinlong; Chen, Chao; Li, Ming; Xi, Chanjuan (Beilstein Journal of Organic Chemistry, 2015)
A series of functionalized benzimidazo[1,2-c]quinazoline derivatives was obtained in excellent yields under mild conditions through a CuI-catalyzed Ullmann N-arylation starting from easily available starting materials.
Keywords: benzimidazo[1,2-c]quinazoline; (bromophenyl)iodonium salt; copper catalyst; o-cyanoaniline; quinazolin-4(3H)-imine; Ullmann N-arylation

(untitled) - Michael, J. P. (Nat. Prod. Rep., 2008)

(untitled) - Beniddir, M. A.; Le Borgne, E.; Iorga, B. I.; Loaëc, N.; Lozach, O.; Meijer, L.; Awang, K.; Litaudon, M. (J. Nat. Prod., 2014)

(untitled) - Horton, D. A.; Bourne, G. T.; Smythe, M. L. (Chem. Rev., 2003)

(untitled) - Sang, P.; Xie, Y.; Zou, J.; Zhang, Y. (Org. Lett., 2012)

(untitled) - Khajavi, M. S.; Rad-moghadam, K.; Hazarkhani, H. (Synth. Commun., 1999)

(untitled) - Insuasty, B. A.; Torres, H.; Quiroga, J.; Abonia, R.; Rodriguez, R.; Nogueras, M.; Sánchez, A.; Saitz, C.; Alvarez, S. L.; Zacchino, S. A. (J. Chil. Chem. Soc., 2006)

(untitled) - Xu, S.; Lu, J.; Fu, H. (Chem. Commun., 2011)

(untitled) - Liu, Q.; Yang, H.; Jiang, Y.; Zhao, Y.; Fu, H. (RSC Adv., 2013)

(untitled) - Lamazzi, C.; Léonce, S.; Pfeiffer, B.; Renard, P.; Guillaumet, G.; Rees, C. W.; Besson, T. (Bioorg. Med. Chem. Lett., 2000)

(untitled) - Rohini, R.; Shanker, K.; Reddy, P. M.; Ho, Y.-P.; Ravinder, V. (Eur. J. Med. Chem., 2009)

(untitled) - Frère, S.; Thiéry, V.; Bailly, C.; Besson, T. (Tetrahedron, 2003)

(untitled) - Molina, P.; Alajarin, M.; Vidal, A. (Tetrahedron Lett., 1988)

(untitled) - Pang, X.; Chen, C.; Su, X.; Li, M.; Wen, L. (Org. Lett., 2014)

(untitled) - Pang, X.; Lou, Z.; Li, M.; Wen, L.; Chen, C. (Eur. J. Org. Chem., 2015)

(untitled) - Wang, Y.; Chen, C.; Peng, J.; Li, M. (Angew. Chem., Int. Ed., 2013)

(untitled) - Su, X.; Chen, C.; Wang, Y.; Chen, J.; Lou, Z.; Li, M. (Chem. Commun., 2013)

(untitled) - Wang, Y.; Chen, C.; Zhang, S.; Lou, Z.; Su, X.; Wen, L. (Org. Lett., 2013)

(untitled) - Zhou, F.; Guo, J.; Liu, J.; Ding, K.; Yu, S.; Cai, Q. (J. Am. Chem. Soc., 2012)

(untitled) - Jones, G. O.; Liu, P.; Houk, K. N.; Buchwald, S. L. (J. Am. Chem. Soc., 2010)

(untitled) - Hassan, J.; Sévignon, M.; Gozzi, C.; Schulz, E.; Lemaire, M. (Chem. Rev., 2002)

(untitled) - Corbet, J.-P.; Mignani, G. (Chem. Rev., 2006)

(untitled) - Wen, L.-R.; Yuan, W.-K.; Li, M. (J. Org. Chem., 2015)

(untitled) - Huang, X.; Yang, H.; Fu, H.; Qiao, R.; Zhao, Y. (Synthesis, 2009)

(untitled) - Wan, J.-P.; Wang, H.; Liu, Y.; Ding, H. (Org. Lett., 2014)

(untitled) - Liu, Y.; Wan, J.-P. (Chem. – Asian J., 2012)